Addressing no hunger and zero poverty: a global perspective / Nur Azlina Mohamad Zahari - Mohamad Zahari, Nur Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The Sustainable Development Goals (SDGs) formulated by the United Nations provide a comprehensive framework for promoting sustainable development globally, with No Hunger (Goal 2) and Zero Poverty (Goal 1) as fundamental objectives. Despite significant advancements in poverty reduction and food security, substantial challenges persist. Approximately 690 million individuals worldwide suffer from chronic hunger, while over 700 million people live in extreme poverty, surviving on less than $1.90 per day. The coexistence of hunger and poverty creates cyclical patterns of deprivation that undermine human dignity and impede socioeconomic progress. This article aims to elucidate the complex interplay of factors contributing to hunger and poverty, provide strategic recommendations to address these issues, and highlight initiatives worldwide that strive toward achieving these ambitious goals.